HATI NURANI (CONSCIENCE) DALAM GEREJA BARAT DARI ERA PATRISTIK HINGGA SKOLASTIK - HERMAWAN, PETER (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2022)
Since the Stoic, conscience has been the subject of discussion. The Stoics argued thatconscience or syneidesis is the knowledge of goodness and self in relation to goodness.In the New Testament Scriptures, St. Paul discusses conscience (syneidesis) asknowledge of moral values and actions themselves. In the Western Church, consciencehas been discussed since the Patristic and Scholastic. This conscience in both eras isdivided into synderesis and conscience. In this Patristic era, St. Jerome thought thatsynderesis was a spark of conscience. Meanwhile, St. Augustine called the conscience(synderesis) a natural tribunal to recognize good and evil.Whereas in the Scholastic era, Peter Lombard only revisited the commentary on thebook of Ezekiel from St. Jerome in the context of discussing the role of the will. St.Thomas Aquinas calls synderesis a natural disposition or habit, while conscience is anact of judgment involving synderesis. St. Thomas Aquinas discusses synderesis andconscience in the mind. This is in contrast to St. Bonaventure associates consciencewith intellect, while synderesis lies with the will. This paper will also discuss therelationship between the discussion of conscience between the figures of the Patristicera and the Scholastic era as mentioned above.